2008
DOI: 10.3922/j.psns.2008.2.004
|View full text |Cite
|
Sign up to set email alerts
|

The effects of early protein malnutrition and environmental stimulation on behavioral and biochemical parameters in rats.

Abstract: The present study investigated the effects of protein malnutrition and environmental stimulation on biochemical and behavioral parameters in rats. The concentrations of polyamines in the frontal cortex, striatum, and hippocampus, as well as plasma corticosterone levels, were measured. The exploratory behavior was analyzed using the elevated plus-maze (EPM) test. Rats received either 16% (well-nourished -W) or 6% (malnourished -M) protein diets and were divided into stimulated or non-stimulated groups. Malnutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 52 publications
(62 reference statements)
1
10
0
6
Order By: Relevance
“…The suggested reasons for the impaired cognitive function in protein undernourished animals include stress, physical weakness due to poor nutrition and lack of sufficient protein components for normal neurodevelopment leading to cognitive and behavioral problem in animals (Yanai et al, 2004). Moreover, Sampaio et al (2008) reported that low protein diet increased the levels of plasma corticosterone; the increase in which has been linked to anxiety relief. Their finding confirmed our earlier report on elevated plus maze (EPM) cognitive function test that low protein diet reduces anxiety and/or impulsiveness (Alamy and Bengelloun, 2012) which has been associated with decreased in basal extracellular dopamine level.…”
Section: Discussionmentioning
confidence: 99%
“…The suggested reasons for the impaired cognitive function in protein undernourished animals include stress, physical weakness due to poor nutrition and lack of sufficient protein components for normal neurodevelopment leading to cognitive and behavioral problem in animals (Yanai et al, 2004). Moreover, Sampaio et al (2008) reported that low protein diet increased the levels of plasma corticosterone; the increase in which has been linked to anxiety relief. Their finding confirmed our earlier report on elevated plus maze (EPM) cognitive function test that low protein diet reduces anxiety and/or impulsiveness (Alamy and Bengelloun, 2012) which has been associated with decreased in basal extracellular dopamine level.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,43 Although the exposition of the dams to a low protein diet can result in a stress condition during the lactation period and, thus, produce alterations in the maternal behavior in response to the pup's demands, previously reported results showed that these possible effects appears to be transient and restricted to the social behavior procedures, with no evident effects on experimental models of anxiety in rats. 7,15,16,18,19,30,39,40 Thus, it is suggested that possible alterations in the behavior of the animals nursed by malnourished dams did not influenced their behavior in the EPM. In contrast, it is suggested that this lower anxiety and/or higher impulsivity can be the result of deleterious effects of early protein malnutrition in the development and maturation of the structures involved in behavioral inhibition, such as the septum, the hippocampus, and the amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 In this study, the stress caused by malnutrition in rats exposed to the EPM can be observed through the increased CORT levels in rats submitted to early protein malnutrition as compared with the well-nourished ones, suggesting an alteration of the organism's stress response as previously demonstrated. 7 It is also known that the individual experience, as the environmental stimulation, in the period of the CNS development, also alters the activity of the HPA axis. 53,54 However, in this study it was not possible to observe any significant statistical difference in CORT levels between stimulated and non-stimulated animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations